PENGARUH PEMANFAATAN MEDIA INTERAKTIF BERBASIS PERMAINAN EDUKATIF UNTUK MENINGKATAN MOTIVASI BELAJAR SISWA SD DI ERA DIGITAL - Satria Saudale; Gerardus Mayorga; Tresilia Amun; Sisilia Eli (STKIP Subang, 2026)
The purpose of this study is to determine how far the learning motivation of elementary school students in this digital era increases in using interactive media based on educational games. The method used is a quasi-experimental method with a pretest-posttest design in this design students are given an initial test to determine the level of student learning motivation and ends with a final test to see changes in student learning motivation when using educational games, the subjects of the study are fifth grade students at SDN Oebobo 2. From research that has been conducted at SD Oebobo 2 there is a slight increase in student learning motivation in using interactive media based on games in the learning process in the classroom due to internal and external factors that do not support. Keywords: interactive media, educational games, learning motivation